Research on the Influence of Wheel Tread Wear on Pinion and Rack Contact State of Rack-rail Trains - Lei Huanhuan; Zhao Jiadong; Zhao Yukai; Shi Lubing; Li Zhiyuan; Yue Zihao (Jixie chuandong)
Aiming at the problem that it is difficult to explore the contact state law of racks and pinions under the condition of rack-rail train wheel tread wear, a calculation model of rack and pinion tooth surface contact stress considering wheel tread wear is proposed based on the Hertz contact theory. Firstly, the contact relationship of racks and pinions under wheel tread wear is analyzed, the change law of key parameters of contact stress calculation with wheel wear is obtained, and the contact stress calculation model of racks and pinions considering wheel wear is constructed in combination with the Hertz contact theory. Then, the rack and pinion parameters of an engineering are selected for calculation, the tooth surface contact stress distribution in the wear cycle is obtained, and the contact stress data of the pinions and racks and of different wear quantities and different contact positions are obtained through 27 sets of finite element simulation tests, which are compared with the above calculation model results. Finally, the above calculation model is used to further analyze the internal mechanism and key factors of wheel wear affecting the contact stress law. The results show that the maximum relative error between the model results and the simulation calculation results is 7.71%, which verifies the accuracy of the calculation model. The greater the wear of the wheel tread is, the greater the contact stress near the meshing entry point of the rack and pinion will be; and the influence mechanism is that the radius of curvature of the drive gear near the meshing entry point is sharply reduced by wheel wear. Increasing the initial center distance and the rack tooth top fillet influence coefficient can reduce the influence of the wheel tread wear. The height adjustment period can also be appropriately reduced to optimize the contact state situation.